Probabilistic Inventory Model Using All Unit Discount Factor and Inflation - Mohammad Soleh; Arinal Haque; Yuslenita Muda (Jurnal Fourier, 2021)
Inflation causes the price per unit of goods to rise in the future. To offset inflation, companies can take advantage of discounts provided by suppliers. But ordering goods must be adjusted according to demand to avoid storage costs. This study describes a probabilistic supply model with demand at a time with a Gamma distribution and waiting for the discount and inflation factors. Backorder conditions in this model is assumed. The research produces a probabilistic inventory model and an algorithm to obtain the optimal number of orders and optimal ordering times for items that are all discounted and inflated with Gamma distribution demand.